Studies on coordination chemistry and bioactivity of Cu(II), Cd(II) and Zn(II) complexes containing some nitrogen-sulphur donor ligands - Kasbollah, Azahari (2001)
Several Schiff bases of S-benzyldithiocarbazate (SBDTC) and S-methyldithiocarbazate (SMDTC) have been synthesised. Complexes of Cu(II), Cd(II) and Zn(II) with the pyridine-2-carboxaldehyde Schiff base of SBDrC were prepared. The compounds were characterised by elemental analyses and various physico-chemical techniques. The Schiff bases and the metal complexes were tested for cytotoxicity and antimicrobial and antioxidant activities. Cytotoxic screenings were carried out against T-lymphoblastic leukaemia cells (CEM-SS) and colon cancer cells (HI -29). The antimicrobial screenings were carried out against four bacteria and four fungi. The antioxidative assay was carried out using the ferric thiocyanate (FTC) method. The Cu(II) and Cd(II) complexes were four coordinate while the Zn(II) complex was six coordinate.